Sunterpreneur: The Role of MSMEs in Economic Development Innovation in Urban Areas - Maya Desvita Utari (Global Writing Academica Researching and Publishing, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in urban economic development, particularly in filling the gaps left by large businesses. However, the centralized development of Jakarta in the central and southern regions has created significant disparities, especially in North Jakarta, characterized by high poverty rates, informal settlements, disaster vulnerability, and limited basic infrastructure. This context restricts access to inclusive economic opportunities for vulnerable groups in the urban peripheries, forming the background for the emergence of the Sunterpreneur Program. This study aims to examine the Sunterpreneur MSME innovation in Sunter Jaya Sub-District, Tanjung Priok, North Jakarta, to understand its urgency and interaction with the local socio-economic environment as a solution to opportunity and economic gaps. The program is a collaboration between the Sunter Jaya community and the Corporate Social Responsibility (CSR) of PT Pertamina Patra Niaga Integrated Terminal Jakarta. This study adopts a qualitative single case study design, with data collected through in-depth interviews, literature review, and secondary data. The findings indicate that Sunterpreneur has successfully accommodated vulnerable groups such as the elderly (15%), female breadwinners (33%), the unemployed (19%), persons with disabilities (22%), and pregnant women (11%). Future plans for digital marketing are expected to further strengthen equal opportunities for all, contributing to business sustainability and improved quality of life for vulnerable groups in Sunter Jaya.